(untitled) (Journal of Economic Additions, 2019)
The volatility in stock exchanges are one of the most debated issues in modern financial and economic literature, especially after the openness and financial integration of the global economy and the recurrence of financial crises. This study aims to measurement Efficient of Arab stock exchanges at the weak leve, The study included four Arab stock exchanges: Saudi Arabia, Abu Dhabi, Qatar and Algeria during the period 01-01-2007 to 31-12-2017, using daily data for stock indices, We apply Stationarity and Independence models. The study concludes that the returns of Arab stock exchanges Do not follow normal distribution and do not Random walk, This means that the Arab stock markets are inefficient at the weak level. Keywords: Capital market efficiency, Random walk, Fat taille, Martingale model, Arab stock exchanges. Jel Classification Codes: C5, G15, E30 , M20